Noninvasive and Quantitative Assessment of In Vivo Fetomaternal Interface Angiogenesis Using RGD-Based Fluorescence. (10th July 2014) - Keramidas, M.; Lavaud, J.; Sergent, F.; Hoffmann, P.; Brouillet, S.; Feige, J.-J.; Coll, J.-L.; Alfaidy, N.
Abstract : Angiogenesis is a key process for proper placental development and for the success of pregnancy. Although numerous in vitro methods have been developed for the assessment of this process, relatively few reliable in vivo methods are available to evaluate this activity throughout gestation. Here we report an in vivo technique that specifically measures placental neovascularization. The technique is based on the measurement of a fluorescent alpha v beta 3 (α v β 3 ) integrin-targeting molecule called Angiolone-Alexa-Fluor 700. The α v β 3 integrin is highly expressed by endothelial cells during the neovascularization and by trophoblast cells during their invasion of the maternal decidua. Angiolone was injected to gravid mice at 6.5 and 11.5 days post coitus (dpc). The fluorescence was analyzed one day later at 7.5 and 12.5 dpc, respectively. We demonstrated that (i) Angiolone targets α v β 3 protein in the placenta with a strong specificity, (ii) this technique is quantitative as the measurement was correlated to the increase of the placental size observed with increasing gestational age, and (iii) information on the outcome is possible, as abnormal placentation could be detected early on during gestation. In conclusion, we report the validation of a new noninvasive and quantitative method to assess the placental angiogenic activity, in vivo .